Advances in the Cathode Materials for Lithium Rechargeable Batteries. Issue 7 (8th November 2019) - Lee, Wontae; Muhammad, Shoaib; Sergey, Chernov; Lee, Hayeon; Yoon, Jaesang; Kang, Yong‐Mook; Yoon, Won‐Sub
Abstract: The accelerating development of technologies requires a significant energy consumption, and consequently the demand for advanced energy storage devices is increasing at a high rate. In the last two decades, lithium‐ion batteries have been the most robust technology, supplying high energy and power density. Improving cathode materials is one of the ways to satisfy the need for even better batteries. Therefore developing new types of positive electrode materials by increasing cell voltage and capacity with stability is the best way towards the next‐generation Li rechargeable batteries. To achieve this goal, understanding the principles of the materials and recognizing the problems confronting the state‐of‐the‐art cathode materials are essential prerequisites. This Review presents various high‐energy cathode materials which can be used to build next‐generation lithium‐ion batteries. It includes nickel and lithium‐rich layered oxide materials, high voltage spinel oxides, polyanion, cation disordered rock‐salt oxides and conversion materials. Particular emphasis is given to the general reaction and degradation mechanisms during the operation as well as the main challenges and strategies to overcome the drawbacks of these materials. Abstract : Cathode materials : Developing new types of cathode materials is the best way towards the next‐generation of rechargeable lithium batteries. To achieve this goal, understanding the principles of the materials and recognizing the problems confronting the state‐of‐the‐art cathode materials are essential prerequisites.